Mampukah publikasi akuntansi lingkungan menjadi pengungkit kinerja keuangan - Setiyanto, Arga Rizki; Haryanto, Sugeng; Sunardi, Sunardi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The main goal of a company is profit. A great company will find the best method to make profit and also preserve nature. The objective of this study is to determine how a firm's size and age affect its financial performance through the use of environmental accounting disclosure levels. This study is a combined study with quantitative information. The object of this study is the manufacturing industry on the BEI. The results of this study are company size, age, and environmental accounting disclosure have no direct influence on the financial performance. This study also found that the level of environmental accounting disclosure is directly influenced by company size and age. In addition, this study also shows that the impact of firm size and firm age on a company's financial performance can be lowered when a company uses the disclosure strategy of environmental accounting.